Cost-Effectiveness of Population Level and Individual Level Interventions to Combat Non-communicable Disease in Eastern Sub-Saharan Africa and South East Asia: A WHO-CHOICE Analysis - Melanie Y. Bertram; Daniel Chisholm; Rory Watts; Temo Waqanivalu; Vinayak Prasad; Cherian Varghese (Kerman University of Medical Sciences, 2021)
Background  To determine the health system costs and health-related benefits of interventions for the prevention and control of non-communicable diseases (NCDs), including mental health disorders, for the purpose of identifying the most cost-effective intervention options in support of global normative guidance on the best-buy interventions for NCDs. In addition, tools are developed to allow country contextualisation of the analyses to support local priority setting exercises. Methods  This analysis follows the standard WHO-CHOICE (World Health Organization-Choosing Interventions that are Cost-Effective) approach to generalized cost-effectiveness analysis applied to two regions, Eastern sub-Saharan Africa and South-East Asia. The scope of the analysis is all NCD and mental health interventions included in WHO guidelines or guidance documents for which the health impact of the intervention is able to be identified and attributed. Costs are measured in 2010 international dollars, and benefits modelled beginning in 2010, both for a period of 100 years. Results  There are many interventions for NCD prevention and management that are highly cost-effective, generating one year of healthy life for less than Int. $100. These interventions include tobacco and alcohol control policies such as taxation, voluntary and legislative actions to reduce sodium intake, mass media campaigns for reducing physical activity, and treatment options for cardiovascular disease (CVD), cervical cancer and epilepsy. In addition a number of interventions fall just outside this range, including breast cancer, depression and chronic lung disease treatment. Conclusion  Interventions that represent good value for money, are technically feasible and are delivered for a low per-capita cost, are available to address the rapid rise in NCDs in low- and middle-income countries. This paper also describes a tool to support countries in developing NCD action plans.